RESEARCHING THERMAL DISSOCIATION OF SPIRIT OXIDE TO OBTAIN HYDROGEN UNDER THE INFLUENCE OF CONCENTRATED SOLAR RADIATION - Sulaymonov Sulton Xamidovich; O‘rinboyev Raximjon Ravshanovich (American Journals Publishing, 2023)
Nowadays, more than 45% of this rapidly growing global energy demand is met by renewable fuels. Despite their ease of use, fossil fuels are the main source of anthropogenic emissions of greenhouse gases and other pollutants, which ultimately have a serious impact on the environment and public health. In addition, fossil fuel resources are limited and unevenly distributed around the world, creating additional concerns about the reliability and security of energy supply. Solar energy, a clean, freely available and almost inexhaustible source of energy, appears as an attractive candidate in this context. However, the large-scale use of this renewable resource is associated with a diluted, intermittent and uneven distribution of solar radiation around the world. Thus, to overcome these obstacles, research on solar thermochemical processing aims to identify and develop convenient thermochemical conversion methods to efficiently store continuous solar energy in the form of high-energy-density chemical bonds.
Keywords: Renewable fuels, energy supply, thermochemical conversion, thermochemical cycles, solar-fuel energy conversion, moderate temperatures, thermal contraction.